The Economic Contribution Of Soya Beans Production In Gusau Town 2000-2020 (Zien Journal of Social Sciences and Humanities, 2025)
The paper socio-economic of soyabeans production in Gusau town, 2000-2022” traces the historical origin of soyabean production in America, Asia and Africa. It showcase that the introduction and production of soyabean in Gusau town with which resulted to the production of employment opportunities and accumulation of capital among the producers of the crop. The paper also argued that the new crop largely dominated other cash crop both in external and internal consumption in the town under review, the significance of soyabeans production in the area the town was also discussed. Finally, the paper pinpointed some problem militating against the production of soyabeans in Gusau.